2018
DOI: 10.1002/jbm.b.34038
|View full text |Cite
|
Sign up to set email alerts
|

Aerogels made of chitosan and chondroitin sulfate at high degree of neutralization: Biological properties toward wound healing

Abstract: In this study, highly neutralized, highly porous, and ultralight polymeric aerogels prepared from aqueous colloidal suspensions of chitosan (CS) and chondroitin sulfate (ChS) nanocomplexes, formulated as quasi-equimolar amounts of both, are described. These aerogels were designed as healing agents under the inspiration of minimizing the amount of matter applied to wounds, reducing the electrostatic potential of the material and avoiding covalent cross-linkers in order to decrease metabolic stress over wounds. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…As shown in the videos (video S1, video S2), the microfibers were rapidly hydrated, and the material were dispersed in small pieces into the medium. Materials with similar behavior when exposed to biorelevant media have been proposed for in vitro/in vivo testing for wound healing purposes [32,34,38] and/or to be enriched with active molecules for therapeutic purposes [39,40,41]. Furthermore, other interesting characterizations regarding the interplay between cells and solid materials and obtaining the stiffness have been published.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in the videos (video S1, video S2), the microfibers were rapidly hydrated, and the material were dispersed in small pieces into the medium. Materials with similar behavior when exposed to biorelevant media have been proposed for in vitro/in vivo testing for wound healing purposes [32,34,38] and/or to be enriched with active molecules for therapeutic purposes [39,40,41]. Furthermore, other interesting characterizations regarding the interplay between cells and solid materials and obtaining the stiffness have been published.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the strategy for this type of formulations is (i) to formulate INC that provides good balance of charges and intimate mixing of oppositely charged polymeric species and (ii) to fabricate low-density sponges by freeze-drying (avoiding cryoprotectants). This has several advantages for better manipulation, such as high stability, easy storage and transportation [38], together with high therapeutic potential [7,8,32,34,38,39,41] despite their low stiffness and high lability toward hydration (see video S1, video S2). Importantly, the hydrated material stands as a gel-like mucus (if intending to dry INC by freeze-drying and further reconstitute them through hydration, cryoprotectants are required [36,48,49]), and cell cultures studies (done following the ISO 10993-5 guidelines) correspond to the cellular response to this hydrated hydrogel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chitosan has many attractive properties including biocompatibility, biodegradability, non-toxicity, remarkable affinity to proteins, bacterial resistance, and hemostaticity [ 18 ]. It is available in different forms (films, gels, sponges, fibers, nanoparticles, nanofibers), and thus is suitable for diverse applications in tissue engineering [ 19 ], promoting the healing process of soft and hard connective tissues [ 20 ]. Recently, in vitro studies have suggested that chitosan could promote cartilage-specific protein expression and reduce inflammatory and catabolic mediator production by chondrocytes [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, bone tissue engineering uses 3D printed scaffolds of regular porosity and shape, which include inorganic nanoparticles as bioactive agents, in order to provide an adequate environment to bone regeneration [11,12,13,14,15]. Highly porous scaffolds with less ordering, based on the ice-segregated ionic self-assembly of complementary charged polysaccharides, have been obtained by freeze-drying for dermis regeneration [16,17].…”
Section: Introductionmentioning
confidence: 99%